Prevalence and intensity of soil-transmitted helminth infections among school-aged children in five districts in Uganda. - Benjamin Tinkitina; Prudence Beinamaryo; Hilda Kyarisiima; Betty Nabatte; Moses Arinaitwe; Alfred Mubangizi; Paul Emerson; Kristin M Sullivan (Public Library of Science (PLoS), 2024)
Background Soil-transmitted helminth (STH) infections, commonly caused by roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Necator americanus and Ancylostoma duodenale), were widespread among Ugandan schoolchildren in the late 1990s and early 2000s. Since 2003, the Ugandan Ministry of Health has administered biannual preventive chemotherapy to children aged 1-14 years to control these infections. Twenty years after the program's inception, there is scant data to show the long-term impact of these national deworming efforts. Methods To estimate the prevalence and intensity of STH infections among 10-14-year-old primary school children, school-based, cross-sectional surveys were conducted in November 2023 across five districts (Kamwenge, Sheema, Adjumani, Lamwo, and Zombo). Sixty-five children from five schools per district were selected for inclusion. Fecal egg counts were determined using the Kato-Katz microscopy technique, performed in duplicate by trained laboratory technicians. Results The survey findings revealed a high prevalence of any STH infection in Kamwenge District (21.2%, 95% confidence limits (CL): 5.7%, 36.6%), while the remaining four districts exhibited lower prevalences, ranging from 0.4% (95% CL: 0.0%, 1.2%) in Adjumani District to 5.6% (95% CL: 0.0%, 11.4%) in Sheema District. The prevalence of moderate-to-heavy-intensity infections was below 1% across all districts. A. lumbricoides was identified infrequently. Hookworm infections were primarily identified in the western districts of Kamwenge and Sheema, while T. trichiura infections were common only in Kamwenge District. Hookworm and T. trichiura infections were uncommon in the northern districts of Adjumani, Lamwo, and Zombo. Conclusions These surveys suggest that morbidity due to STH infections among schoolchildren may be well controlled in these five districts, as evidenced by low moderate-to-heavy-intensity infection prevalence. However, the prevalence of any intensity infection remains elevated in some districts, indicating the need for continued preventive chemotherapy distribution. A reduction from biannual treatment may be warranted in four districts, per World Health Organization recommendations.